System Genetics Including Causal Inference Identify Immune Targets for Coronary Artery Disease and the Lifespan. (24th February 2021) - Bon-Baret, Valentin; Chignon, Arnaud; Boulanger, Marie-Chloé; Li, Zhonglin; Argaud, Deborah; Arsenault, Benoit J.; Thériault, Sébastien; Bossé, Yohan; Mathieu, Patrick
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Randomized clinical trials indicate that the immune response plays a significant role in coronary artery disease (CAD), a disorder impacting the lifespan potential. However, the identification of targets critical to the immune response in atheroma is still hampered by a lack of solid inference. Methods: Herein, we implemented a system genetics approach to identify causally associated immune targets implicated in atheroma. We leveraged genome-wide association studies to perform mapping and Mendelian randomization to assess causal associations between gene expression in blood cells with CAD and the lifespan. Expressed genes (eGenes) were prioritized in network and in single-cell expression derived from plaque immune cells. Results: Among 840 CAD-associated blood eGenes, 37 were predicted causally associated with CAD and 6 were also associated with the parental lifespan in Mendelian randomization. In multivariable Mendelian randomization, the impact of eGenes on the lifespan potential was mediated by the CAD risk. Predicted causal eGenes were central in network. FLT1 and CCR5 were identified as targets of approved drugs, whereas 22 eGenes were deemed tractable for the development of small molecules and antibodies. Analyses of plaque immune single-cell expression identified predicted causal eGenes enriched in macrophages ( GPX1, C4orf3 ) and involved in ligand-receptor interactions ( CCR5 ). Conclusions: We identified 37 blood eGenes predicted causally associated with CAD. The predicted expression for 6 eGenes impacted the lifespan potential through the risk of CAD. Prioritization based on network, annotations, and single-cell expression identified targets deemed tractable for the development of drugs and for drug repurposing.